2011
DOI: 10.3732/ajb.1000267
|View full text |Cite
|
Sign up to set email alerts
|

A sequential approach using genetic and morphological analyses to test species status: The case of United States federally endangered Agalinis acuta (Orobanchaceae)

Abstract: Through this successive approach, we found insufficient evidence to support the evolutionary distinctiveness of the listed taxon A. acuta . We recommend that it be synonymized under A. decemloba and also conclude that the taxon that would now include A. acuta is deserving of protection under the Endangered Species Act.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Funk & Omland (2003) found that non‐monophyletic species were found in 23% of cases in a study of more than 2000 species of animals. Many cases of non‐monophyletic species have also been detected in plants (e.g., Fazekas & al., 2008; Pettengill & Neel, 2010; Arca & al., 2012). According to our identifications, Micropholis egensis and M. madeirensis were polyphyletic, and M. guyanensis and M. venulosa were both polyphyletic and paraphyletic in the three analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Funk & Omland (2003) found that non‐monophyletic species were found in 23% of cases in a study of more than 2000 species of animals. Many cases of non‐monophyletic species have also been detected in plants (e.g., Fazekas & al., 2008; Pettengill & Neel, 2010; Arca & al., 2012). According to our identifications, Micropholis egensis and M. madeirensis were polyphyletic, and M. guyanensis and M. venulosa were both polyphyletic and paraphyletic in the three analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the current phylogenetic analyses reflected a clear separation of the sampled individuals into two distinct clades, which also presented distinct morphological traits (see introduction). A growing number of studies have argued that concordance among independent sources of molecular data can be a criterion for identifying distinct species (Groeneveld, Weisrock, Rasoloarison, Yoder, & Kappeler, ; Leavitt, Johnson, & St. Clair, ; Pettengill & Neel, ; Weisrock et al, ). In our study, the concordance of divergence between morphological, mitochondrial locus and nuclear DNA analyses should be viewed as the most convincing evidence supporting P. gravivox and P. swinhoei as distinct species.…”
Section: Discussionmentioning
confidence: 99%